Predictive value for increased red blood cell distribution width in unprovoked acute venous thromboembolism at the emergency department - Febra, Cláudia (2023)
Acute venous thromboembolism (VTE) is a common worldwide disease admitted to emergency departments (ED), usually presenting as pulmonary embolism or lower limb deep vein thrombosis (DVT). Due to the lack of typical clinical and biomarker diagnostic features of unprovoked VTE, early identification is challenging and has direct consequences on correct treatment delay. Longitudinal, prospective, observational study. Patients admitted to ED with a suspicion of unprovoked acute VTE between October 2020 and January 2021 were included. Clinical and laboratorial variables were compared between VTE positive and negative diagnoses. Red cell distribution width (RDW) cut point was determinate through a receiver operating characteristic analysis. RDW accuracy, sensitivity, and specificity were calculated. Fifty-eight patients were analyzed. And 82.8% of suspected patients with VTE were diagnosed with an acute thrombotic event confirmed by imaging examination. In patients with VTE, RDW at admission in ED was higher than with other diagnosis, respectively, 14.3% (13.2-15.1) and 13.5% (13.0-13.8). Platelet count was the only additional characteristic that revealed difference between the 2 groups (264x109/L for VTE and 209x109/L for non-VTE). Logistic regression models showed good discriminatory values for RDW & GE;14%, with an area under the curve (AUC) = 0.685 (95% confidence interval, 0.535-0.834). These findings were more pronounced in isolated DVT, with a sensitivity of 76.9%, specificity 100%, and accuracy 85.7%. Our study demonstrated a significant association between an early high RDW and the diagnosis of acute unprovoked DVT. RDW & GE; 14% has an independent predictor of unprovoked VTE in adult patients.